A 25-year-old male with appendicular agenesis: A case report and literature review. Issue 1 (February 2017) - Shah, Tajammal A.
لملخص: إن عدم تكون الزائدة الدودية منذ الولادة خلقيا أو عدم وجودها هو نادر للغاية. تعرض هذه الحالة مريضا ذكرا عمره ٢٥ عاما ظهرت عليه أعراض وعلامات التهاب الزائدة الدودية الحاد. تعذر العثور على الزائدة الدودية على الرغم من عملية الاستكشاف الجراحي الواسع. ولم تظهر فحوص مابعد الجراحة شيئا غير طبيعي، وتم تشخيص المريض كحالة آلام في البطن غير محددة وعدم تخلق الزائدة الدودية. Abstract: Congenital agenesis or absence of vermiform appendix is extremely rare. This case report entails a 25-year-old male who developed symptoms and signs of acute appendicitis. Despite an extensive surgical exploration, the vermiform appendix could not be found. The postoperative investigation did not reveal any abnormality, and the patient was diagnosed as a case of nonspecific abdominal pain (NSAP) and appendicular agenesis.